Multiphase management of sodium imbalance following traumatic brain injury: a case-based review - Vinson James; Laura Nimkoff (BMC Pediatrics)
Abstract Background This review article discusses a case of sodium imbalance and fluid dysregulation in a patient with traumatic brain injury (TBI), progressing through phases including mannitol-induced osmotic diuresis, arginine vasopressin deficiency (central diabetes insipidus), and syndrome of inappropriate antidiuresis (SIAD), before eventual resolution with euvolemia. The timeline of clinical interventions, laboratory trends, and diagnostic insights highlights the complexity of managing sodium and fluid balance in TBI patients. Objective To illustrate the diagnostic and management challenges of a pediatric TBI case complicated by the sequential development of osmotic diuresis, arginine vasopressin deficiency, syndrome of inappropriate antidiuretic hormone secretion (SIAD), and subsequent stabilization. Methods We present a detailed case report of a child with severe TBI who experienced multiple phases of sodium and fluid dysregulation, necessitating vigilant monitoring and dynamic management adjustments. Results The patient initially developed profound polyuria due to mannitol-induced osmotic diuresis, which obscured the emerging arginine vasopressin deficiency. The transition to SIAD further complicated management, requiring careful fluid and sodium correction. This case underscores the importance of close monitoring in post-TBI patients to detect evolving endocrine disturbances that necessitate timely interventions. Conclusion The sequential manifestation of osmotic diuresis, arginine vasopressin deficiency, SIAD, and eventual stabilization in a single patient is a rare and complex occurrence. This case emphasizes the need for dynamic fluid and electrolyte management, with ongoing assessment to tailor interventions appropriately. Our findings highlight the critical role of multidisciplinary teams in optimizing patient outcomes in pediatric TBI cases.